2020
DOI: 10.5114/hpr.2020.97346
|View full text |Cite
|
Sign up to set email alerts
|

Music therapy for preterm infants and their parents during NICU stay and beyond: current recommendations for clinical practice in Poland

Abstract: health psychology report • volume 8(3),  review article There is preliminary evidence that music therapy plays a beneficial role for preterm infants and their primary caregivers during the neonatal period; however, available research considers mostly cohorts from North and South Americas, Australia, Israel and certain western European countries, excluding Poland. Remembering that music, and therefore music therapy, is highly culturally dependent, there is no "perfect program package" that can be directly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
3
8
0
1
Order By: Relevance
“…The normal functioning of twins after TTTS syndrome in terms of cognitive and motor functions can be attributed to early tactile and vestibular stimulation in the prenatal period, which is consistent with studies indicating normal cognitive, motor, and emotional functioning [ 42 , 47 , 48 , 49 , 50 , 51 , 52 ]. The twins differ slightly in cognitive functioning and general intelligence: the functioning of K, the recipient, was at the upper limit of the average level, while that of B, the donor, was at the average level.…”
Section: Discussionsupporting
confidence: 87%
“…The normal functioning of twins after TTTS syndrome in terms of cognitive and motor functions can be attributed to early tactile and vestibular stimulation in the prenatal period, which is consistent with studies indicating normal cognitive, motor, and emotional functioning [ 42 , 47 , 48 , 49 , 50 , 51 , 52 ]. The twins differ slightly in cognitive functioning and general intelligence: the functioning of K, the recipient, was at the upper limit of the average level, while that of B, the donor, was at the average level.…”
Section: Discussionsupporting
confidence: 87%
“…The field of music therapy also developed treatment options to support mothers who gave birth prematurely, and they cover all three aspects that are described above, although most of these methods focus on treatment within the NICU [31][32][33][34][35][36][37][38]. However, there is currently a shortage of music therapy-based methods that care for mothers and preterm infants, and address their psychosocial needs post-NICU hospitalization [39,40].…”
Section: Existing Treatment Methodsmentioning
confidence: 99%
“…Music therapy programs that are intended specifically for NICU-discharged dyads are, to date, quite scarce [40]. Palazzi et al (2020) [54] reported of their work with a mother and her preterm baby, during their NICU hospitalization and 4 months after their discharge.…”
Section: Existing Treatment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ANS maturation and behavioral responsivity in preterm infants is largely conditioned by gestational age [29], which is also a medical factor determining the starting point of many early therapy services in the NICU. In the field of NICU-MT it has been recommend that interventions should not be started earlier than 26 weeks [47].…”
Section: Potential Variables Related To the Mechanisms In Nicu Music Therapy During Kangaroo Carementioning
confidence: 99%